Cattell-Braasch Maneuver: A Gadget to Manipulate Abdominal Aortic Aneurysm in a Patient with a Left-Sided Inferior Vena Cava - Akiko Tobe; Takuro Shirasu; Takatoshi Furuya; Motoki Nagai; Yukihiro Nomura (Case Reports in Surgery)
A 76-year-old man was diagnosed with abdominal aortic aneurysm and a left-sided inferior vena cava. He underwent open surgery, and we employed the Cattell-Braasch maneuver to approach the abdominal aortic aneurysm from the right side. This enabled securing of the abdominal aortic aneurysm neck without mobilizing or dissecting the inferior vena cava. His postoperative course was uneventful. Although abdominal aortic aneurysm is typically approached from the left side in open surgery, approaching from the right side is beneficial in patients with abdominal aortic aneurysm and a left-sided inferior vena cava.